Технологічні відкриття - Сирадоєв, А. О. (ХНУРЕ, 2020)
The article gives a detailed analysis of technological discoveries of Ukraine. Technology is an important factor in every modern state, consequently it is so important to understand this topic well in our time. Much attention is given to modern technological discovers.
Keywords: культурне розмаїття; українознавство; традиції; культура